ED50 and ED95 of Intrathecal Isobaric Levobupivacaine Coadministered with Fentanyl for Transurethral Resections: Randomized, Double-blind Trial - Karslı, N. D.; Subaşi, D.; Terzioğlu, B.; Turan, G.; Ekinci, O. (Drug Research, 2015)
Levobupivacaine use is progressively increased for intrathecal anesthesia in transurethral resections. The aim was to determine ED50 and ED95 of intrathecal isobaric levobupivacaine by addition of 25 mcg fentanyl for patients undergoing transurethral resections.A total of 100 patients undergoing transurethral resections with ASA I–III, were randomized to groups receiving intrathecal 0.5% isobaric levobupivacaine in doses of 6, 8, 10, 12 or 14 mg in equal volumes with 25 mcg intrathecal fentanyl addition. Sensorial block level was determined by pinprick and motor block by Bromage scale.Mean onset time of sensorial block in 6 mg group was significantly longer than that of sensorial block in 10 mg, 12 mg and 14 mg groups (p<0.01), 8 mg was longer than 12 mg and 14 mg (p<0.01), and 10 mg onset time of sensorial block was significantly longer than 12 mg and 14 mg (p<0.01). Mean onset time of T10 sensory level in 6 mg group was significantly longer than mean onset time of T10 sensory level in 10 mg, 12 mg and 14 mg (p<0.01), the mean onset time of T10 sensory level in 8 mg group was also significantly longer than that of 12 mg, 14 mg groups (p<0.01). ED50 and ED95 of levobupivacaine coadministered with 25 mcg fentanyl were 7.32 mg and 10.88 mg, respectively.Levobupivacaine with opioid co-administration can be used in doses considerably lower than doses proposed for routine use as it is a safe drug depending on its hemodynamic effects, side effects.
Keywords: levobupivacaine; effective dose 50%; effective dose 95%; transurethral resection